The Role of GSH Supplements in Maturation Media in Improving the Bali Cattle Oocyte Fertility by in Vitro Technique - Ary, Kana; Idrus, Muhammad; Sonjaya, Herry; Firmiaty, Sri (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
In the in vitro oocyte culture process, oxidative stress often occurs, which produces free radicals, so it was necessary to add the antioxidant glutathione (GSH). This research aimed to determine the fertility level of Bali cattle oocytes by adding glutathione (GSH) to the medium maturation. The study was conducted at the In Vitro Embryo Production Laboratory, Institute for Research and Community Service (LPPM) Building, Hasanuddin University in March-May 2023. The study consisted of 4 treatments with the addition of GSH (0 mM, 0.5 mM, 1 mM, and 1.5 mM) with 6 repetitions. The mature oocytes were then subjected to in vitro fertilization. The results showed that the highest fertilization rate (2 PN/Pronucleus) was significantly higher (P <0.05) in the treatment with the addition of 1-1.5 mM GSH to medium maturation, compared to 0.5 mM and without GSH addition, whereas  fragmented oocytes (0 PN), (1PN) and (>2 PN) were not significantly different. This study concluded that adding 1.5 mM glutathione (GSH) to the maturation medium showed the best results, namely 72.26 % fertilized oocytes.